Human capital, income diversification and bank performance–an empirical study of East African banks - Peter Nderitu Githaiga (Emerald Publishing Limited, 2020)
The purpose of this paper is to examine whether income diversification moderates the relationship between human capital and bank performance.The study uses a sample of 53 banks and panel data for the years 2010–2018. The hypotheses are tested through hierarchical multiple regression and the choice between fixed effect and random effect estimation is based on the results of the Hausman test.The study finds that human capital and income diversification significantly influence bank performance; however, the direction of the causality varies. While human capital has a positive effect, income diversification has a negative effect. Additionally, the interaction term has a negative and significant effect on bank performance, inferring that income diversification has an antagonistic effect on the human capital and bank performance relationship. For the control variable, liquidity and asset quality negatively affects bank performance while capitalization has a positive effect.Human capital was measured as human capital efficiency (HCE), which is a quantitative measure of human capital, hence future studies can use qualitative measures. Also, the study focused on commercial banks in East Africa, future researcher may possibly consider other regions and industries, which would shed more insights.The results of this paper provide valuable insights. Bank managers can get a better understanding of the impact of human capital on bank performance, and the need to invest more in human capital development. Further, the study cautions bank managers that engaging in non-lending activities might destroy the economic value of human capital and ultimately lower performance. The study also recommends that policymakers should address the obstacles to banks' income diversification, for instance relaxing regulations restricting diversification; this might enable banks to leverage related financial service activities for optimal utilization of human capital and improve banks' profitability.While a good number of previous studies investigated the direct effect of human capital and income diversification on the performance of banks, this study examines the moderating role of income diversification on the relationship between human capital and performance of banks in East Africa.